Impact of selected characteristics of SMES on the capital structure - Belas, Jaroslav; Gavurova, Beata; Toth, Peter (Journal of Business Economics and Management, 2018)
The optimal capital structure is a key precondition for business, even though defining the optimal capital structure is difficult. The available studies present many different and mutually contradictory factors that need to be taken into account in the strategic financial decisions of managers. Their importance and intensity are different for individual business entities. Given the specificities of companies in the SME segment, achieving an optimal capital structure is a challenging task as there is no model of an optimal capital structure that can be universally applied in corporate practice. For this reason, we decided to realize our research. The main aim of the paper is to identify determinants of the SME’s capital structure. We studied the impact of four determinants: region, business area, number of employees and business duration, on the manager’s decisions about capital structure in the enterprise. Our research is based on the database ‘Albertina’, which consist of all SME in the Czech Republic. We applied ordinal logistic regression and estimated five models. These models were used to predict attitude of SME to the capital structure. Analysis was done in R Software. The main finding is that the size of the company measured by the number of employees effects its attitude to volume of foreign and own capital used to finance its activities. Analysis also showed that entrepreneurs with longer duration of taking their business prefer more foreign capital than their own capital. Business area and region where enterprise is located do not significantly affect capital structure.